A Skin Lipidomics Study Reveals the Therapeutic Effects of Tanshinones in a Rat Model of Acne - Chen, Tingting; Zhu, Zhaoming; Du, Qunqun; Wang, Zhuxian; Wu, Wenfeng; Xue, Yaqi; Wang, Yuan; Wu, Yufan; Zeng, Quanfu; Jiang, Cuiping; Shen, Chunyan; Liu, Li; et al. (Frontiers in Pharmacology, 2021)
Tanshinone (TAN), a class of bioactive components in traditional Chinese medicinal plant Salvia miltiorrhiza, has antibacterial and anti-inflammatory effects, can enhance blood circulation, remove blood stasis, and promote wound healing. For these reasons it has been developed as a drug to treat acne. The purpose of this study was to evaluate the therapeutic effects of TAN in rats with oleic acid-induced acne and to explore its possible mechanisms of action through the identification of potential lipid biomarkers. In this study, a rat model of acne was established by applying 0.5 mL of 80% oleic acid to rats’ back skin. The potential metabolites and targets involved in the anti-acne effects of TAN were predicted using lipidomics. The results indicate that TAN has therapeutic efficacy for acne, as supported by the results of the histological analyses and biochemical index assays for interleukin (IL)-8, IL-6, IL-β and tumor necrosis factor alpha. The orthogonal projection of latent structure discriminant analysis score was used to analyze the lipidomic profiles between control and acne rats. Ninety-six potential biomarkers were identified in the skin samples of the acne rats. These biomarkers were mainly related to glycerophospholipid and sphingolipid metabolism, and the regulation of their dysfunction is thought to be a possible therapeutic mechanism of action of TAN on acne.